A Preliminary Examination of Child Well-Being of Physically Abused and Neglected Children Compared to a Normative Pediatric Population. (February 2015) - Lanier, Paul; Kohl, Patricia L.; Raghavan, Ramesh; Auslander, Wendy
Federal mandates require state child welfare systems to monitor and improve outcomes for children in three areas: safety, permanency, and well-being. Research across separate domains of child well-being indicates maltreated children may experience lower pediatric health–related quality of life (HRQL). This study assessed well-being in maltreated children using the Pediatric Quality of Life Inventory (PedsQL 4.0), a widely used measure of pediatric HRQL. The PedsQL 4.0 was used to assess well-being in a sample of children ( N = 129) receiving child welfare services following reports of alleged physical abuse or neglect. We compared total scores and domain scores for this maltreated sample to those of a published normative sample. Within the maltreated sample, we also compared well-being by child and family demographic characteristics. As compared with a normative pediatric population, maltreated children reported significantly lower total, physical, and psychosocial health. We found no significant differences in total and domain scores based on child and parent demographics within the maltreated sample. This preliminary exploration indicates children receiving child welfare services have significantly lower well-being status than the general child population and have considerable deficits in social and emotional functioning. These findings support continued investment in maltreatment prevention and services to improve the well-being of victims of maltreatment.